STUDI FAUNA VEKTOR MALARIA DI DAERAH ENDEMIS MALARIA DESA WAY MULI KABUPATEN LAMPUNG SELATAN - Dita Amita; Fernalia Fernalia; Rika Yulendasari (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2019)
THE EFFECT OF DEEP BREATHING RELAXATION ON THE INTENSITY OF PAIN IN POSTOPERATIVE PATIENTS SECTIO CAESAREA AT BENGKULU HOSPITALThis research in purpose to explain the effect of deep breathing relaxation to intensity of pain in postoperative patients sectio caesarea at Bengkulu Hospital. This research use quantitative method with pre eksperimen design without control group. The samples taken with accidental sampling technique with total sample 30 people. Instrument that use intensity of pain scale questionnaire that normative. Result of data analysis indicate that there is a strong effect to intensity of pain (p=0,000) after deep breating relaxation. Recommendation of this study to nursing health service kindly more attention and doing implementation of deep breathing relaxation on patients sectio caesarea.